2008
DOI: 10.1002/adfm.200700634
|View full text |Cite
|
Sign up to set email alerts
|

Block Copolymer ‘Stealth’ Nanoparticles for Chemotherapy: Interactions with Blood Cells In Vitro

Abstract: Passive targeting is one of the approaches to reduce the side effects in intravenous chemotherapeutic administration. This is usually achieved by using so‐called ‘stealth’ particles as carriers, such that the particles can avoid uptake by cells of the reticulo endothelial system (RES) and thus enhance their blood lifetime. To date, there have been no studies of the contribution of various factors to the uptake of particles by the RES, although there is general agreement that a hydrophilic particle surface is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…Multifunctional nanostructured drug carriers, constructed through skillful integration of polymeric materials and drugs, have been proposed to break through biological barriers and deliver cargo drugs to specific sites, especially to solid tumors [2][3][4][5][6][7][8]. By an enhanced permeability and retention (EPR) effect, these nanosized delivery systems are able to passively accumulate drugs in solid tumors [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Multifunctional nanostructured drug carriers, constructed through skillful integration of polymeric materials and drugs, have been proposed to break through biological barriers and deliver cargo drugs to specific sites, especially to solid tumors [2][3][4][5][6][7][8]. By an enhanced permeability and retention (EPR) effect, these nanosized delivery systems are able to passively accumulate drugs in solid tumors [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] For these reasons, during the past few decades, a great deal of effort has been devoted to invent and discover novel medicinal approaches, including drug-delivery system (DDS). [3][4][5][6][7][8][9][10][11] Many drug-delivery vectors, either viral or nonviral, have been developed in order to improve the performance of many existing anticancer drugs through enhancing their efficacy as well as cellular uptake efficiency to malignant tumor cells. The rapid development in nanotechnology enabled controlled design and synthesis of supramolecular-sized materials and, furthermore, nano-bio convergences open a new era and suggest many possible ways to settle the concerns in cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…After loading with DOX, the oMCN@DOX was subsequently wrapped up by DSPE-mPEG2000 with hydrophobic segments physically absorbed on the surface of the oMCNs and hydrophilic parts as the outer layers, which helped to avoid the recognition of reticuloendothelial system. [15][16][17] In order to confirm that hydrophilic groups and polyethylene glycol were successfully introduced to the MCNs, the FTIR and 1 H-nuclear magnetic resonance spectra were collected, as shown in Figure 2. From the FTIR spectra (Figure 2A), it can be clearly seen that the MCNs exhibited typical related absorption bands of aromatic hydrocarbons at 2,025 cm So the results of FTIR spectra showed that we had succeeded in synthesizing oMCN@PEG.…”
Section: Results and Discussion Synthesis And Characterization Of Omcmentioning
confidence: 99%